Vitamíny a doplňky stravy ve výživě pacientů s poruchami krvetvorby - Chmelařová, Elen (Univerzita Karlova, 1. lékařská fakulta, 2023)
This bachelor's thesis deals with the possible beneficial effects of vitamins, minerals and dietary supplements that could positively influence the course of treatment of blood cancers. In addition to vitamins and minerals, dietary supplements for the purposes of this thesis include various food supplements that can be purchased in pharmacies, as well as foods or spices, herbs and mushrooms that can be purchased in regular grocery stores. The main objective of the study was to find out whether patients take any of these selected supplements during treatment. The secondary aim of this work was to get an idea about the patients' awareness, their choice of food supplements that they purchase and how they themselves evaluate the effect of these supplements on their health status. The theoretical part deals with the brief characteristics of the most common haemato- oncological diseases of patients visiting the specialist departments of the General Faculty Hospital in Prague (VFN). In the theoretical part, this thesis also deals with a total of 57 different supplements (9 vitamins, 6 minerals, 15 food supplements and 27 different foods, spices, herbs and mushrooms) that could have positive effects in the treatment of these serious diseases, as reported in the scientific literature and also in the popular. Tato bakalářská práce se zabývá možnými prospěšnými účinky vitamínů, minerálů a doplňků stravy, které by mohly svým účinnými látkami positivně ovlivnit průběh léčby nádorových onemocnění krve. Za doplňky stravy jsou vedle vitamínů a minerálů považovány pro účely této práce různé potravinové doplňky, které je možné zakoupit v lékárnách, dále potraviny nebo koření, byliny a houby, které je možné zakoupit v běžných ochodech s potravinami. Hlavním cílem práce bylo zjistit, zda pacienti užívají některé z těchto vybraných suplementů v průběhu léčby. Druhotným cílem této práce bylo získat představu o informovanosti pacientů, o jejich výběru potravinových doplňků, které si oni sami zakoupí a jak hodnotí oni sami vliv ...